Inheriting Justice:Reading Myself Through an Erased History - Corrin, Jeffrey (My University, 2020)
The over-arching goal of this project is to instill hope for activists and social workers, while simultaneously exploring the narrative of my Great-Grandmother, Mrs. Marguerite Emily Cartwright, whose activist story has never truly been told. Through the use of storytelling and thematic analysis, this research will present the reader with an opportunity to explore the tools and strategies that one woman used to make a profound and lasting influence on disability services, the study of disability and persons with disabilities throughout Ontario in the 1940’s and onwards. The Study of Disability, Disability Studies and Social Justice Studies, along with storytelling literature, are both broad albeit unique areas of knowledge. This unique thesis is based on the analysis of my family’s archives of Mrs. Cartwright’s activism, through original journal entries and newspaper clippings, along with letters and personal correspondences Mrs. Cartwright wrote to prominent North American politicians, offering a window into the mind of the activist herself. Through the use of storytelling and thematic analysis, this paper explores how the themes of wielding personal power, inheriting a moral sense of justice, and the history of disability services in Ontario contributed to the telling of Mrs. Cartwright’s untold story. An analysis of Mrs. Cartwright’s activist strategies demonstrated the intersectionality of disability, critical theory, feminism and justice studies, and the use of self in advocacy. Lastly, I discuss how my own sense of social justice, epistemology and practice of social work has been impacted by the telling of this story.
Keywords: Activism; Intellectual Disability; Masie Cartwright; Vulnerability; Social Change; Social Work; History of Disability